Arbuscular Mycorrhiza Changes the Impact of Potato Virus Y on Growth and Stress Tolerance of Solanum tuberosum L. in vitro - Deja-Sikora, Edyta; Kowalczyk, Anita; Trejgell, Alina; Szmidt-Jaworska, Adriana; Baum, Christel; Mercy, Louis; Hrynkiewicz, Katarzyna (Frontiers in Microbiology, 2020)
Under the field conditions crop plants interact with diverse microorganisms. These include beneficial (symbiotic) and phytopathogenic microorganisms, which jointly affect growth and productivity of the plants. In last decades, production of potato (Solanum tuberosum L.) suffers from increased incidence of potato virus Y (PVY), which is one of most important potato pests. Arbuscular mycorrhizal fungi (AMF) are common symbionts of potato, however the impact of mycorrhizal symbiosis on the progression of PVY-induced disease is scarcely known. Therefore, in the present study we investigated the effect of joint PVY infection and mycorrhizal colonization by Rhizophagus irregularis on growth traits of the host potato plant (cv. Pirol). The tested PVY isolate belonged to N-Wilga strain group, which is considered to be predominant in Europe and many other parts of the world. The viral particles were concentrated in the leaves, but decreased the root growth. Furthermore, the infection with PVY evoked prolonged oxidative stress reflected by increased level of endogenous H2O2. AMF alleviated oxidative stress in PVY-infected host plants by a substantial decrease in the level of shoot- and root-derived H2O2, but still caused asymptomatic growth depression. It was assumed that mycorrhizal symbiosis of potato might mask infection by PVY in field observations.